The body image "problem" on social media: Novel directions for the field. (June 2022) - Sharp, Gemma; Gerrard, Ysabel
Abstract: Social media is a highly popular and interactive environment which has many benefits, but research has shown that its use is also associated with body image concerns. Leaked internal survey findings in September 2021 from Instagram provide some support for negative impacts on body image of teenage girls especially. In this short communication, we discuss the complexities of moderating social media platforms which aim to protect users from potentially harmful body image focused content. Several strategies have been employed and we specifically examine the moderation of pro-eating disorder hashtags (e.g., #thinspiration) and hiding of "Like" counts on Instagram in particular. We find that both are quick technical "fixes" that do not effectively address these long-standing and complex issues on social media. We provide suggestions for novel avenues of research, including that body image researchers are excellently positioned to propose specific suggestions for content moderation strategies that may actually be effective. Social media companies know that they have a major problem on their hands, as the leaked findings demonstrate, and so they may be more receptive than they have ever been to novel research findings from our community. Highlights: Social media use is associated with body dissatisfaction. The moderation of content on social media is a complex issue. Content moderation strategies involving pro-eating disorder hashtags are ineffective. We should study how people use different social media platforms in more depth. We should make research-based recommendations for content moderation strategies.